Investigating the experiences of family caregivers who shackle people with mental disorders - Kusumawaty, Ira; Yunike, Yunike (Frontiers in Psychiatry, 2023)
The mental health literacy gap has resulted in the shackling of people with mental illness by family caregivers. Although shackling violates human rights and impacts physical and psychological health, it still occurs in some countries, such as Indonesia. An in-depth study using the family function approach is needed to distinguish the components behind the application of shackling by families to find solutions to prevent shackling. Thus, this study aims to identify family functions in people with mental disorder (PWMD) care and to create a family care model for PWMD in accordance with the family function approach and recommendations for preventing shackling. This qualitative research used a phenomenological approach, involving eight participants who are family caregivers and live with their patients. Triangulation was conducted by applying interviews with four health cadres to confirm previous information. The process of in-depth interviews and observational data collection methods was carried out until reaching data saturation. The data analysis process used Collaizi's pattern to formulate three main themes, namely confinement as the final solution for the family, the specifics of confinement, and the family's purpose for confinement. The conclusion is that shackling occurs due to a lack of understanding of the impact of shackling and the various limitations experienced, so shackling becomes the last resort when dealing with patients. Peer support is very important for families to prevent the confinement of mentally ill family members. Technological advances are an inherent need in everyday life and must support family caregivers with mental disorders.